2002
DOI: 10.1097/01.asn.0000031721.19801.7c
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol Inhibits Acid-Induced Bone Resorption In Vitro

Abstract: Abstract. Metabolic acidosis increases urine calcium excretion without an increase in intestinal calcium absorption, resulting in a net loss of bone mineral. In vitro, metabolic acidosis has been shown to initially induce physicochemical mineral dissolution and then enhance cell-mediated bone resorption. Acidic medium stimulates osteoblastic prostaglandin E 2 production, which mediates the subsequent stimulation of osteoclastic bone resorption. Glucocorticoids are also known to decrease bone mineral density, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…The magnitude of this acid-induced increase in medium prostaglandin E 2 levels of primary bone cells was comparable to that observed in cultured calvariae incubated in acid medium. We also found that cortisol inhibits acid-induced bone resorption through a decrease in osteoblastic prostaglandin E 2 production [113]. These results suggest that acid-induced, cell-mediated calcium efflux from bone is regulated, at least partly, by an increase in endogenous prostaglandin E 2 production.…”
Section: Role Of Prostaglandin Productionsupporting
confidence: 62%
“…The magnitude of this acid-induced increase in medium prostaglandin E 2 levels of primary bone cells was comparable to that observed in cultured calvariae incubated in acid medium. We also found that cortisol inhibits acid-induced bone resorption through a decrease in osteoblastic prostaglandin E 2 production [113]. These results suggest that acid-induced, cell-mediated calcium efflux from bone is regulated, at least partly, by an increase in endogenous prostaglandin E 2 production.…”
Section: Role Of Prostaglandin Productionsupporting
confidence: 62%
“…Metabolic acidosis also stimulates osteoblasts to release prostaglandins, which in turn inhibits osteoblastic activity and stimulates osteoclastic function [99][100][101][102]. Glucocorticoids inhibit the production of prostaglandins by osteoblasts, and this in turn inhibits the acidosis-induced bone resorption [103]. Furthermore, since acid loading in normal animals and humans is associated with hypercalciuria and phosphaturia, it has been suggested that bone is a major site for the extracellular buffering of the retained acid [92,97,[104][105][106][107][108][109].…”
Section: Direct Effects Of Acidosis On Bonementioning
confidence: 99%
“…Some environmental factors including heat shock (Hsp90) (28), hypoxia (29), shear stress (30) and ozone stress (31) also have shown to upregulate PGE 2 production. PGE 2 production is inhibited by antioxidant flavonoid (32), gamma-tocopherol (33), vitamin D (34), estrogen (35), dexamethason (36), cortisol (37), or chitosan (38). Food components such as conjugated linoleic acid (39), oleic acid (40), soybean isoflavone (41), tea polyphenols (42), or caffeic acid (43) also depresses PGE 2 production.…”
Section: Regulation On Pge 2 Productionmentioning
confidence: 99%
“…The down regulation of COX-2 expression is largely mediated by the inhibition of MAPK, PKC, AP-1, NF-kappaB and many other intracellular signaling. Caffine (43), alpha-tocopherol (50), ceramide (53), PGJ 2 (54), cortisol (37), dexathmasone (55), PPAR-gamma ligand Accompanying with the up or down regulation of COX-2 expression, the major mechanism(s) and intracellular signaling components involved are provided. ↑ or ↓ denotes activation or inhibition, respectively (56), retinoic acid (57), estradiol (58) or vitamin D (34) depresses COX-2 expression.…”
Section: Cox-2 Regulation 411 Cox-2 Expressionmentioning
confidence: 99%